2018
DOI: 10.1051/matecconf/201822902002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing community resilience to natural disaster and climate change in Maitara Island, North Maluku-Indonesia

Abstract: VVHVVLQJ FRPPXQLW\ UHVLOLHQFH WR QDWXUDO GLVDVWHU DQG FOLPDWH FKDQJH LQ 0DLWDUD ,VODQG 1RUWK 0DOXNX,QGRQHVLD 0RKDPPDG 5LGZDQ /HVV\ -HIU\ %HPED DQG 1DQL 1DJX 0DULQH 6FLHQFH 'HSDUWPHQW .KDLUXQ 8QLYHUVLW\ 7HUQDWH ,QGRQHVLD &LYLO 'HSDUWPHQW .KDLUXQ 8QLYHUVLW\ 7HUQDWH ,QGRQHVLD $EVWUDFW 6PDOO ,VODQGV IDFH VRPH RI WKH PDLQ SUREOHPV RI DQ\ FRDVWDO DUHD GXH WR FOLPDWH FKDQJH DQG QDWXUDO GLVDVWHUV 7KLV VWXG\ DLPV WR DQDO\]H WKH UHVLOLHQFH RI FRDVWDO FRPPXQLWLHV RQ D VPDOO LVODQG LQ WHUPV RI GLVDVWHUV DQG FOLPDWH FKDQJH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Previous studies (Moreno et al 2019 ; Lessy et al 2018 ; Taupo 2018 ; Rampengan et al 2014 ; Tita 2014 ) have shown that local community members, particularly fishers, are directly or indirectly affected by disasters in small islands, reflecting our findings in this study that the fishing community managed to survive despite the magnitude of catastrophe with no report of casualties. Indeed, community resilience plays a vital role during the response period as underscored by, among others, Moreno et al ( 2019 ), Johansen et al ( 2016 ), and Rampengan et al ( 2014 ).…”
Section: Disaster Risk Reduction Management Structure In Guimarassupporting
confidence: 76%
“…Previous studies (Moreno et al 2019 ; Lessy et al 2018 ; Taupo 2018 ; Rampengan et al 2014 ; Tita 2014 ) have shown that local community members, particularly fishers, are directly or indirectly affected by disasters in small islands, reflecting our findings in this study that the fishing community managed to survive despite the magnitude of catastrophe with no report of casualties. Indeed, community resilience plays a vital role during the response period as underscored by, among others, Moreno et al ( 2019 ), Johansen et al ( 2016 ), and Rampengan et al ( 2014 ).…”
Section: Disaster Risk Reduction Management Structure In Guimarassupporting
confidence: 76%
“…Collaboration among stakeholders is required to minimize the risk. There are many cases where the local community is involved in disaster management, which has proven effective (Buchori et al, 2022;Lessy et al, 2018;Mane, 2019). Local community members generally have knowledge and experiences about local culture and histories that are valuable in disaster risk management (Kumaraswamy et al, 2015).…”
Section: Disaster Managementmentioning
confidence: 99%
“…It is important to address barriers to disaster preparedness and enhance community resilience. Resilience in relation to natural disasters encompasses 3 common themes, first, the ability to absorb or accommodate the stressor or adverse event; second, the ability to recover and return to healthy levels of functioning (and not necessarily predisaster functioning); third, the ability to learn, adapt, or transform in response to disaster exposure [1, [31][32][33][34][35]. The Australian Disaster Resilience Index was created to assess disaster resilience in Australia and it was found that most of the population of Australia lived in areas that were assessed as having "moderate" resilience for natural disasters, with "low" disaster resilience observed primarily in remote areas [1].…”
Section: Introductionmentioning
confidence: 99%